2017
DOI: 10.1021/acsami.7b11325
|View full text |Cite
|
Sign up to set email alerts
|

Facile Coordination-Precipitation Route to Insoluble Metal Roussin’s Black Salts for NIR-Responsive Release of NO for Anti-Metastasis

Abstract: A facile and general coordination-precipitation method is developed to synthesize insoluble metal Roussin's black salts (Me-RBSs) as a new type of NIR-responsive NORMs. The weak-field ligand coordination of metal-RBS brings a NIR absorption effect of Me-RBSs, and further gives rise to the NIR adsorption-dependent NIR-responsive NO release profile. Intratumoral NIR-responsive release of NO effectively inhibits the growth and metastasis of the metastatic breast cancer. Aqueous insolubility of Me-RBSs ensures low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Upon NIR (808 nm) laser irradiation, the photothermal conversion of polydopamine layer rapidly increased the local temperature and triggered the NO release from SNO (Figure e), which further reversed the MDR of MCF‐7/ADR cancer cells, enhanced the chemotherapeutic efficacy of DOX, and caused photoinduced hyperthermia as indicated by the significantly inhibited tumor growth (Figure f) . Qian et al reported a facile coordination–precipitation approach to fabricate insoluble metal Roussin's black salts, which performed a NIR adsorption‐dependent NIR‐responsive NO releasing for significantly inhibiting the growth and metastasis of metastatic breast cancer …”
Section: Nitric Oxide (No)‐generating Ggnsmentioning
confidence: 99%
“…Upon NIR (808 nm) laser irradiation, the photothermal conversion of polydopamine layer rapidly increased the local temperature and triggered the NO release from SNO (Figure e), which further reversed the MDR of MCF‐7/ADR cancer cells, enhanced the chemotherapeutic efficacy of DOX, and caused photoinduced hyperthermia as indicated by the significantly inhibited tumor growth (Figure f) . Qian et al reported a facile coordination–precipitation approach to fabricate insoluble metal Roussin's black salts, which performed a NIR adsorption‐dependent NIR‐responsive NO releasing for significantly inhibiting the growth and metastasis of metastatic breast cancer …”
Section: Nitric Oxide (No)‐generating Ggnsmentioning
confidence: 99%
“…[117] Since gasotransmitters can serve as endogenous gaseous messengers to regulate physiological functions, gas therapy is considered a "green" treatment paradigm that has negligible side effects on normal tissues. NO gasotransmitters have direct antitumor effects at high concentrations; therefore, encapsulating NO donors (e.g., nitroimidazole, [118] S-nitrosothiol (SNO), [86a] and Roussin's black salt (RBS) [119] ) into lanthanide nanoparticles seems to be a promising approach to control the NO concentration for X-ray-induced gas therapy because lanthanide nanoparticles can act as a scintillator and convert high-energy X-rays into UV-vis light, further triggering NO release from NO donors. Reproduced with permission.…”
Section: X-ray-activated Gas Therapymentioning
confidence: 99%
“…The NIR‐responsive nanomedicine had been widely studied in recent years (L. Chen et al, ; J. Peng et al, ; X. Tang et al, ). For example, a mesoporous magnetic gold “nanocluster” (MMGNCs) was built to load doxorubicin (DOX) in 2014 (J. Peng et al, ).…”
Section: Physical‐responsive Nanomedicinementioning
confidence: 99%